8(-2z+5)=7(2+z)+3(z-1)
First, Distribute:
-16z+40=14+7z+3z-3
Now, combine like terms:
-16z+40=11+10z
Now Isolate the variable (add 16z to both sides and subtract 11):
29=26z
Now divide both sides by 26:
29/26=z
Therefore:
z = 29/26
2007-02-27 19:47:09
·
answer #1
·
answered by Derrick_k 2
·
0⤊
0⤋
8(-2z + 5) = 7(2 + z) + 3(z - 1)
-16z + 40 = 14 + 7z + 3z - 3
40 - 14 + 3 = 10z + 16z
29 = 26z
z = 29/26
(would have preferred a whole number answer!)
2007-02-28 04:33:34
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
8(-2z+5) = 7(2+z) + 3(z-1)
-16z + 40 = 14 + 7z + 3z - 3
-16z - 7z - 3z = 14 - 40 - 3
-26z = -29
-29 / -26 = z
1.1153846 = z
2007-02-28 03:56:20
·
answer #3
·
answered by leachim 3
·
0⤊
0⤋
8(-2z+5)=7(2+z)+3(z-1)
-16z+40=14+7z+3z-3
26z=29
z=29/26
2007-02-28 04:09:50
·
answer #4
·
answered by phani 1
·
0⤊
0⤋
z = 29/26
2007-02-28 03:54:43
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
8(-2z+5)=7(2+z)+3(z-1)
First multiply (-2z+5) by 8, (2+z) by 7 and (z-1) by 3.
We get -16z+40 = 14+7z+3z-3
Now subtract 7z from both sides of the equation
-16z+40-7z = 14+7z-7z+3z-3
i.e., -16z+40-7z = 14+3z-3 (because 7z-7z=0).
Now subtarct 3z fronm both sides
-16z+40-7z-3z = 14+3z-3z-3
i.e., -16z+40-7z-3z = 14-3 (because 3z-3z=0).
i.e., -16z-7z-3z+40=11
Now subtract 40 from both sides
-16z-7z-3z+40-40=11-40
i.e., -16z-7z-3z=11-40 (because 40-40=0)
i.e., -26z=-29
now multiply both sides by -1
-1*-26z=-1*-29
i.e., 26z=29
Divide both sides by 26
we get 26z/26=29/26
So, z=29/26.
2007-02-28 04:00:14
·
answer #6
·
answered by Jabir 1
·
0⤊
0⤋
29/26 is right ..!
2007-02-28 03:49:22
·
answer #7
·
answered by HariSeldon 2
·
1⤊
0⤋
I dont know,mathematics sucks!!
2007-02-28 03:48:49
·
answer #8
·
answered by Cadpigfriend 2
·
0⤊
1⤋
solve it by multiplication
2007-02-28 04:32:37
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋